A Sand Fly, Lutzomyia shannoni Dyar (Insecta: Diptera: Psychodidae: Phlebotomine) - Rajinder S. Mann; Phillip E. Kaufman; Jerry F. Butler (EDIS)
EENY-421, a 5-page illustrated fact sheet by Rajinder S. Mann, Phillip E. Kaufman, and Jerry F. Butler, is part of the Featured Creatures collection. It describes this subfamily of sand flies that can transmit several disease-causing organisms of humans and other animals — its distribution, description, life cycle, hosts, medical importance, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.